The influencing factors of changes in medication compliance of hypertensive patients in some areas of China - Tai-Sen HAN; Chen-Chen ZHAI; Zhen-Huan LUO; Jia-Hui GU; Qi BAO; Xiao-Dong GUAN; Lu-Wen SHI (Yixue xinzhi zazhi)
Objective To explore the changes in medication adherence of community dwelling hypertensive patients in six provinces in China, and analyze the influencing factors.Methods Community dwelling hypertensive patients attending 7 county-level community hospitals in 6 provinces in China were selected to undertake a health promotion program consisting of various health management interventions such as use of chronic disease pharmacies, hypertension clinics and drug dispensing services. Descriptive statistics were used to analyze the levels of medication adherence before after the hypertension health promotion program. Univariate analysis and logistic regression were used to analyze the factors that influenced patients' medication adherence.Results A total of 715 hypertension patients who completed the follow-up survey were included in the study. The follow up survey showed that patients' medication adherence increased by 16.2% (P